Screening of drug targets for tuberculosis on the basis of transcription factor regulatory network and mRNA sequencing technology - Wang, Shuai; Yan, Na; Yang, Yue; Sun, Li; Huang, Yingxin; Zhang, Jian; Xu, Guangyu (Frontiers in Molecular Biosciences, 2024)
Background: Tuberculosis is a worldwide epidemic disease, posing a serious threat to human health. To find effective drug action targets for M. tuberculosis, differentially expressed genes in tuberculosis patients and healthy people were screened by mRNA sequencing in this study. A total of 556 differentially expressed genes in tuberculosis patients and healthy people were screened out by mRNA sequencing technology. 26 transcription factors and 66 corresponding target genes were screened out in the AnimalTFDB 3.0 database, and a transcription factor regulatory network was constructed.: Three key transcription factors (TP53, KLF5 and GATA2) and one key gene (AKT1) were screened as new potential drug targets and diagnostic targets for tuberculosis by MCODE cluster analysis, and the key genes and key transcription factors were verified by RT-PCR. Finally, we constructed the and a key factor and KEGG signaling pathway regulatory network to clarify the possible molecular pathogenesis of tuberculosis. Conclusion: This study suggested M. tuberculosis may activate the AKT1 gene expression by regulating transcription factors TP53, KLF5, and GATA2, thus activating the B cell receptor signaling pathway to induce the infection and invasion of M. tuberculosis. AKT1, TP53, KLF5, and GATA2 can be used as new potential drug targets for tuberculosis.